Pathways for School Leaders to Enact Social Justice ... - Honya Bianchini (University of Alberta Library, 2021)
Six years after the Truth and Reconciliation Commission of Canada’s Calls to Action charted changes in policy and practice to advance the process of reconciliation within Canada (2015), authentic progress made in school settings is modest. Approaching the problem of waning attention and commitment to reconciliation education in school settings from a research-based position as well as from the stance of classroom teacher, the author provides insight into the obstacles embedded in educational frameworks, and pathways open to school leaders striving to further levels of awareness and effective action for social justice within schools with an emphasis on students and communities that are First Nations, Métis or Inuit. Examples of critical practices and understandings for teacher leaders and administrators to enact social justice are educator reflection on the beneficiaries of reconciliation education in its current form, in-depth learning about Indigenous worldview and colonial histories, land-based cumulative ...